PENGARUH PENERAPAN STRATEGI PEMBELAJARAN PROBLEM BASED INSTRUCTION DENGAN MEDIA VIRTUAL LABORATORY TERHADAP HASIL BELAJAR SISWA - Eka Juli Tri Saman Tari Br Saragih; Lisa Utami (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2019)
Abstract This research is motivated by the low level of learning outcomes of the students of science class XI at Bernas Binsus State Senior High School Pelalawan Regency. Therefore the experiment research is conducted by pre-test and post-test scheme to discover the effect of problem based instruction learning model by virtual laboratory media toward learning outcomes of class XI students at Bernas Binsus State Senior High School Pelalawan Regency at the subject of buffer solution. The subjects of the research are the students of class XI science in the year of 2015-2016 with two classes as samples: class XI science 3 (experiment) that consists of 28 students and  class XI science 2 (control) that consists of 29 students. The research data is collected by using observation, initial data test which is homogeneitytest and final data test which are pre-test dan post-test, and documentation. To discover the effect of the implementation the learning model toward the learning outcomes, the formula of partial equilibrium (Kp) is employed. The effect differences are analyzed by t test polled varians. Analysis result of initial and final data indicates that t-counting = 2.79 and t-table = 1.67 in the significance rate of 5%. The value of t-counting > t-table that makes Ho is rejected and Ha is accepted. It indicates that there is a correlation of the implementation of Problem Based Instructionlearning model with virtual laboratory media toward learning outcomes of the students of class XI Bernas Binsus State Senior High School Pelalawan Regency at the subject of buffer solution, with the effect of 12.43 %.  Keywords:  Problem Based Instruction, Virtual Laboratory Media, Learning Outcome.